Hypoxia promotes proliferation and inhibits myogenesis in broiler satellite cells - Usuk Jung; Minjeong Kim; Presley Dowker-Key; Simon Noë; Ahmed Bettaieb; Elizabeth Shepherd; Brynn Voy (Poultry Science, 2024)
ABSTRACT: Breast muscle myopathies in broilers compromise meat quality and continue to plague the poultry industry. Broiler breast muscle myopathies are characterized by impaired satellite cell (SC)-mediated repair, and localized tissue hypoxia and dysregulation of oxygen homeostasis have been implicated as contributing factors. The present study was designed to test the hypothesis that hypoxia disrupts the ability of SC to differentiate and form myotubes, both of which are key components of myofiber repair, and to determine the extent to which effects are reversed by restoration of oxygen tension. Primary SC were isolated from pectoralis major of young (5 d) Cobb 700 chicks and maintained in growth conditions or induced to differentiate under normoxic (20% O2) or hypoxic (1% O2) conditions for up to 48 h. Hypoxia enhanced SC proliferation while inhibiting myogenic potential, with decreased fusion index and suppressed myotube formation. Reoxygenation after hypoxia partially reversed effects on both proliferation and myogenesis. Western blotting showed that hypoxia diminished myogenin expression, activated AMPK, upregulated proliferation markers, and increased molecular signaling of cellular stress. Hypoxia also promoted accumulation of lipid droplets in myotubes. Targeted RNAseq identified numerous differentially expressed genes across differentiation under hypoxia, including several genes that have been associated with myopathies in vivo. Altogether, these data demonstrate localized hypoxia may influence SC behavior in ways that disrupt muscle repair and promote the formation of myopathies in broilers.